Availability of Inclusive Health Services for Persons with Disabilities in Indonesia: An Analysis by Facility Type and Region - Salwah Suardi; Muhammad Irvan Nur Iva; Rezki Ramdani (Journal of Scientific Insights, 2026)
Persons with disabilities are at risk of facing structural barriers to accessing health care, yet the availability of disability-friendly services across primary and referral health facilities in Indonesia has not been comprehensively mapped at the national level by facility type and area of residence. This evidence gap limits the formulation of well-targeted health accessibility policies. Objective: This study aimed to analyze the availability of disability-specific services across four types of health facilities, namely Community Health Centers (Puskesmas), Independent Health Worker Clinics/Practices, Health Laboratories, and Hospitals, according to urban and rural area classification in Indonesia. Methods: This was a secondary data analysis employing a descriptive-analytical cross-sectional design, using household data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI) (n=315,646 households). The availability of disability services (Yes/No/Do not know) for each facility type was analyzed according to urban–rural classification, with weighted proportion estimates accounting for sampling weights and the complex survey design (strata and cluster/PSU), followed by Rao–Scott design-adjusted tests of independence. Results: Nationally, the highest proportion of households reporting that a facility provided disability-specific services was found for Hospitals (urban 88.5%; rural 82.1%), while the lowest was found for Independent Health Worker Clinics/Practices (urban 52.3%; rural 38.4%). All facility types showed statistically significantly lower proportions in rural than in urban areas (p